On perspective directions for optimising the structure of chapter 25 of the Criminal Code of the Republic of Belarus - Goloventchik, Marina G. (Journal of the Belarusian State University. Law, 2025)
The article examines the features of the concept of «economic crimes», analyses the doctrinal approaches of both domestic and foreign authors, devoted to the correlation of this concept with the range of socially dangerous acts covered by it. It is noted that all crimes against the order of economic activity cannot be unconditionally attributed to economic crimes. The possibility of placement of individual articles of the current criminal law of the Republic of Belarus and their combination within the framework of new chapters on crimes, the specific objects of which are the corresponding similar social relations, are substantiated.